Distributive principles of economic justice: an Islamic perspective - Zakiyuddin Baidhawy (Indonesian Journal of Islam and Muslim Societies, 2012)
Poverty and impoverishment in the world currently continue to increase as aresult of distributive justice systems and its principles that became the basis ofcontemporary economics did not succeed in allocating and distributing resourcesjustly. Based on this problem, this study aimed at describing the Islamic responseto the problem of distributive injustice, and how necessarily the state played arole in upholding distributive justice. Through the thematic-induction method andthe synthetic analysis, the study finds out several findings as follows. Firstly,Islam formulated three principles of distributive justice as follows: 1) the Distributionof natural and the environmental resources was in the framework of participation;2) the Redistribution of the wealth and the income were joint responsibilityof ascertaining social security, the increase in the capacity and the authorityfor them who were disadvantage; and 3) the Role of the state was certaintythat was complementary for the ethical market in order to guarantees the senseof justice and the achievement of public welfare. Secondly, according to Islam,the process of the redistribution of the wealth and the income aimed at givingsocial security on the fulfillment of basic needs for the poor; strove for the increasein the capacity through education and skills; and increased the poor’sbargaining position through their participation in decision making that was linkedwith their interests and the control on its implementation. Thirdly, the intention of establishing justice was to gain both individual and public welfare and the happiness(al-falah}).Kemiskinan dan pemiskinan di dunia kontemporer terus meningkat sebagai akibatsistem keadilan distributif dan prinsip-prinsipnya yang menjadi basis ekonomisaat ini tidak berhasil dalam mengalokasikan dan memeratakan sumber dayasecara adil. Berdasarkan masalah ini, kajian ini bertujuan untuk menjelaskanrespon Islam atas problem ketidakadilan distributif, dan bagaimana seharusnyanegara ambil peranan dalam menegakkan keadilan distributif. Melalui metodeinduksi-tematik dan analisis sintetik, kajian ini menemukan beberapa hal pentingantara lain. Pertama, Islam telah merumuskan tiga prinsip keadilan distributifsebagai berikut: 1) pemerataan sumber daya alam dan lingkungan dalamkerangka partisipasi; 2) redistribusi kekayaan dan pendapatan dalam rangkamemastikan keamanan sosial, dan meningkatkan kapasitas dan otoritas bagimereka yang kurang/tidak beruntung; dan 3) peran negara merupakan pelengkapbagi pasar yang etis dengan maksud untuk menjamin rasa keadilan dantercapainya kesejahteraan publik. Kedua, menurut Islam, proses redistribusikekayaan dan pendapatan bertujuan untuk memberikan jaminan sosial bagipemenuhan kebutuhan orang miskin; untuk meningkatkan kapasitas merekamelalui pendidikan dan pelatihan; dan meningkatkan posisi tawar kaum miskinmelalui partisipasi dalam pengambilan keputusan yang berkaitan langsung dengankepentingan mereka, serta kendali atas pelaksanaan keputusan tersebut. Ketiga,maksud penegakkan keadilan ialah untuk mewujudkan kesejahteraan sekaliguskebahagiaan individu dan publik.